Catalytic oxidative desulphurization of gasoline using amphiphilic polyoxometalate@polymer nanocomposite as an efficient, reusable, and green organic–inorganic hybrid catalyst. Issue 10 (28th April 2020) - Rezvani, Mohammad Ali; Shaterian, Maryam; Aghmasheh, Masomeh
ABSTRACT: To preparation of ultra-clean gasoline fuel, a new amphiphilic nanocomposite (TBA-SiWMn@PVA) has been successfully synthesized by supporting sandwich-type silicotungstate polyoxometalate ((n-C4 H9 )4 N)7 H5 Si2 W18 Mn4 O68 (TBA-SiWMn) on polyvinylalcohol (PVA) as an efficient catalyst for catalytic oxidative desulphurization (CODS) of gasoline. The synthesized materials were characterized by means of elemental analysis, 113 Mn NMR, 29 Si NMR, XRD, SEM, FT-IR and UV–vis techniques. The catalytic activity of TBA-SiWMn@PVA nanocomposite was tested on real gasoline in the presence of CH3 COOH/H2 O2 as an oxidant and the results were compared with model sulphur compounds at the same conditions. The TBA-SiWMn@PVA nanocomposite was shown excellent catalytic performance and recoverability for ODS of gasoline with high yield. The effects of the reaction time, reaction temperature, dosage and nature of catalyst were investigated. The reaction mechanism and the kinetic parameters of sulphur compounds oxidation were also discussed. The probable mechanism was proposed via the electrophilic mechanism through the formation of a peroxometalate intermediate complex with phase transfer properties. Results were indicated that the kinetics of sulphur oxidation fitted the pseudo-first-order kinetic model. After 5 oxidation runs, the heterogeneous nanocatalyst was separated and recovered easily. GRAPHICAL ABSTRACT: